The Motivation of Using English Language in Instagram Captions - Rahayu Atila; Septhia Irnanda (English LAnguage Study and TEaching, 2021)
Instagram is now a photo and video-sharing social media platform used around the world, and English is increasingly used in captions by non-English speaking Instagram users. This study was aimed to figure out why students at Serambi Mekkah University write English captions on Instagram. This study involved 30 students majoring in English at the University of Serambi Mekkah. The research design used was a descriptive study. To collect data, a close-ended yes-no question questionnaire was distributed online through Google Form. The questionnaire measured the responses in terms of English learning and self-image factors. The results show that the reason students of Serambi Mekkah University used English in their Instagram captions is mainly driven by their need of improving their English proficiency, specifically the spelling and vocabulary. The self-image factor plays a relatively important role too, as half of the participants confessed that they used English in their Instagram post for the sake of being regarded cool and creative. This study suggests that EFL learners use social media not only to improve their English but also to show people their competency in using English.